(untitled) (World Bulletin of Public Health, 2022)
The purpose of this study is clinical and radiographical evaluation of the effect of Algipore (bone substitute material) on the healing of tooth extraction sockets on human. The clinical study carried on sixty patients with bilateral lower third molar teeth indicated for extraction. In one side we packed the socket after extraction by Algipore material, in the other side, the sockets were left to heal spontaneously as a control. The healing of the sockets were evaluated by a transmission densitometer for the X-ray films (Periapical and Orthopantomogram), at one week, one month, three months, and six months postoperatively. The densitometric values showed that the bone formation in the experimental side was faster than the control side. And the transmission densetometer is a reliable method to evaluate the progress of bone healing in tooth extraction sockets